How Leaders’ Psychological Capital Influence Their Followers’ Psychological Capital: Social Exchange or Emotional Contagion - Chen, Qishan; Kong, Yurou; Niu, Jun; Gao, Wenyang; Li, Jieying; Li, Miaosi (Frontiers in Psychology, 2019)
Using a sample of 32 work teams (32 work team leaders and their 321 followers) in Chinese cultural context, this study investigated the relationships between leaders’ and their followers’ psychological capital and the multilevel multiple mediation effects of social exchange and emotional contagion. Structural equation model and hierarchical linear model were applied to analyze the survey data. The results revealed that leaders’ psychological capital had a positive influence on their followers’ psychological capital. Leader-member exchange was the cross-level mediator between leaders’ psychological capital and their followers’. The cross-level mediating effect of leaders’ positive emotions perceived by followers was not significant. The results of this study extended the social exchange theory and enriched researches on leadership. The implication was discussed in details.